Vāsudeva-Śrīkṛṣṇacandra - Śarmā, Dvārakāprasāda (The Chaturvedi prize and library edition series, 1926)
Biographie des Gottes Kṛṣṇa. - Life of Kṛṣṇa in prose, with emphasis on heroic rather than erotic mode